Image of the heroic marriage motive in the Turkic peoples epos - Azhar Shaldarbekova, Nurmira Zhumay, Perizat Ussipbayeva, Shakir Ibrayev, Kuanyshbek Kenzhalin, (Opción, 2020)
The paper considers the features of the heroic marriage motive development in the Turkic peoples epos structure, particularly in the Kazakh epos. Comparative analysis of the epic heritage of the nations (Kazakh, Kyrgyz, Karakalpak, Nogai, Bashkir, etc.) resulted in the fact that the motive is abundantly found in the most ancient epic sources. By incorporating some of the most important components in Kazakh poems, authors conclude that this issue is of great importance to large-scale research.